Model Penanaman Hidroponik Sawi Daging Sistem Wick Sederhana untuk Pemenuhan Gizi Pencegah Stunting - Afib Rulyansah (Abdi Panca Marga, 2019)
This training program is shown to provide new knowledge and information in the mustard farmers sector. The agricultural sector business that was included was owned by the GAPOKTAN groups in Pajarakan Kulon Village. Partners who have problems with the mustard planting system and the fulfillment of nutrition from vegetables to the community. The problems that exist in partners are still not getting the right solution so that in this case solutions can be given in the introduction of new planting models in the mustard growers sector through training in planting mustard greens using a simple Wick Hydroponics System, in order to produce superior types of mustard greens that canard must provide nutritional fulfillment with good and optimal. The existence of problem solving by partners gets new information, training and hands-on practice carried out in each partner's residence to test the trials and continue to run into businesses in the mustard farmers sector Keywords: training, hydroponics, mustard greens, nutrition